Social Interaction in the Multicultural Society of Bandung City: An Inspiration for Interfaith Harmony - Pauzian, Muhamad Hilmi (Sekretariat Badan Moderasi Beragama dan Pengembangan Sumber Daya Manusia (BMBPSDM) Kementerian Agama RI, 2025)
Bandung is a highly diverse city, and Kampung Toleransi in Balonggede Village, Regol District, reflects this diversity. The village was built upon the pluralistic nature of its community, consisting of individuals from various religious backgrounds, as evidenced by three places of worship nearby. In general, communities with diverse backgrounds are often perceived as challenging to interact with harmoniously. However, Kampung Toleransi demonstrates a different pattern of social interaction. This study aims to analyze religious tolerance within social interactions to maintain harmony in Kampung Toleransi. The sociological approach to religion is employed, utilizing Mukti Ali's theories on tolerance and harmony along with George Simmel's theory of social interaction. This qualitative research gathers data through observation, interviews, and documentation. The findings reveal that the values of tolerance in social interactions within Kampung Toleransi are manifested through government policies, the roles of religious leaders, and the application of ideal principles. The forms of interaction include subordination under a single leader, multiple leaders, ideal principles, and individual freedom, all of which reflect the values of religious tolerance. In conclusion, the harmonious interactions in Kampung Toleransi serve as a model for fostering tolerance in social interactions based on community diversity. This model is highly relevant for application in other cities and regions, particularly in West Java and throughout Indonesia.